Rogue, Prisoner, Princess (Of Crowns and Glory-Book 2) - Morgan, Rice (Lukeman Literary, 2016)
"Morgan Rice has come up with what promises to be another brilliant series, immersing us in a fantasy of valor, honor, courage, magic and faith in your destiny. Morgan has managed again to produce a strong set of characters that make us cheer for them on every page....Recommended for the permanent library of all readers that love a well-written fantasy." --Books and Movie Reviews, Roberto Mattos (regarding Rise of the Dragons) ROGUE, PRISONER, PRINCESS is book #2 in Morgan Rice's bestselling epic fantasy series OF CROWNS AND GLORY, which begins with SLAVE, WARRIOR, QUEEN (Book #1). 17 year old Ceres, a beautiful, poor girl from the Empire city of Delos, finds herself forced, by royal decree, to fight in the Stade, the brutal arena where warriors from all corners of the world come to kill each other. Pitted against ferocious opponents, her chances of survival are slim. Her only chance lies in drawing on her innermost powers, and making the transition, once and for all, from slave to warrior. 18 year old Prince Thanos wakes on the isle of Haylon to discover he has been stabbed in the back by his own people, left for dead on the blood-soaked beach. Captured by the rebels, he must crawl his way back to life, find who tried to assassinate him, and seek his revenge. Ceres and Thanos, a world apart, have not lost their love for each other; yet the Empire court teems with lies, betrayal and duplicity, and as jealous royals weave intricate lies, they each, in a tragic misunderstanding, are led to believe the other is dead. The choices they make will determine each other's fate. Will Ceres survive the Stade and become the warrior she was meant to be? Will Thanos heal and discover the secret being withheld from him? Will the two of them, forced apart, find each other again? ROGUE, PRISONER, PRINCESS tells an epic tale of tragic love, vengeance, betrayal, ambition, and destiny. Filled with unforgettable characters and heart-pounding action, it transports us into a world we will never forget, and makes us fall in love with fantasy all over again. "An action packed fantasy sure to please fans of Morgan Rice's previous novels, along with fans of works such as The Inheritance Cycle by Christopher Paolini.... Fans of Young Adult Fiction will devour this latest work by Rice and beg for more." --The Wanderer, A Literary Journal (regarding Rise of the Dragons) Book #3 in OF CROWNS AND GLORY will be released soon!
Keywords: Sci-fi, fantasy; Dobrodružství, napětí, fantasy